Effect of Type and Concentration of Liquid Organic Fertilizer on Growth and Yield of Eggplant (Solanum melongena L.) - Prismaya Andarema; Juli Santoso Pikir; Pangesti Nugrahani (Future Science, 2021)
Eggplant (Solanum melongena L) is a plant that is well known in the wider community. The demand for eggplant is currently increasing. In 2017-2018, eggplant production increased, although it did not meet market demand. One of the causes of eggplant yields not sufficient to market demands is not appropiate of cultivation technique. One of the efforts that can be made to increase the productivity of eggplant is the use of liquid organic fertilizer and the right concentration. The purpose of the research was to find out the effect of liquid organic fertilizer and concentration on the growth and yield of eggplant. The research was conducted on the field of Kenanten village, Puri district, Mojokerto in March 2020 – June 2020. The research is arranged using a Completely Randomized Factorial Design with two factors, firstly the type of liquid organic fertilizer (P) consisting of P0 = Control; P1 = Commercial Liquid Organic Fertilizer; P2 = Kelanalagi Liquid Organic Fertilizer; P3 = Compost tea and concentration (K) consisting of K1 = 4 ml/l water; K2 = 6 ml/l water; K3 = 8 ml/l water. The result showed that there was no interaction between the type of liquid organic fertilizer and the concentration of all observation parameters